ADAPTING THE REGGIO EMILIA APPROACH IN SINGAPORE: ADDRESSING PROFESSIONAL DEVELOPMENT AND TRAINING NEEDS OF PRESCHOOL TEACHERS - Chen Chen; Mohd Nazri Bin Abdul Rahman (PUPIL: International Journal of Teaching, Education and Learning, 2025)
With the ongoing reform of early childhood education in Singapore, the Reggio Emilia Approach (REA) has attracted more attention in the field. This qualitative study explores the practical challenges and professional development needs of preschool teachers in Singapore in implementing the REA. Despite the increasing popularity of the REA, which emphasizes child-centered pedagogy. Research findings from semi-structured interviews with three preschool teachers indicate that teachers face barriers. Challenges include inadequate resources, insufficient training, and cultural differences between the REA philosophy and the prevailing parental expectations of education (focus on academic achievement). This study highlights the need for professional development that not only deepen teachers’ understanding of REA, but also equip them with practical skills to adapt to the cultural expectations of Singaporean education. This study contributes to the discourse on adapting Western educational models in Asian settings and emphasizes the importance of aligning educational innovations with local cultural and educational norms.